2017
DOI: 10.1016/j.addbeh.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of youth internalising and externalising symptom severity on the effectiveness of brief personality-targeted interventions for substance misuse: A cluster randomised trial

Abstract: Conrod, P. J. (2017). The impact of youth internalising and externalising symptom severity on the effectiveness of brief personality-targeted interventions for substance misuse: A cluster randomised trial. Addictive Behaviors. Conrod , The impact of youth internalising and externalising symptom severity on the effectiveness of brief personality-targeted interventions for substance misuse: A cluster randomised trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Such interventions could be delivered in the form of teacher-delivered interactive sessions to raise awareness of the effect of psychological factors on smoking and drinking in secondary schools. Successful randomized controlled trials targeting maladaptive coping strategies and personality traits, including hopelessness, sensation seeking, anxiety and sensitivity, have been conducted in school settings in order to prevent alcohol and drug use (with no specific reference to tobacco consumption though) in high-risk adolescents [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions could be delivered in the form of teacher-delivered interactive sessions to raise awareness of the effect of psychological factors on smoking and drinking in secondary schools. Successful randomized controlled trials targeting maladaptive coping strategies and personality traits, including hopelessness, sensation seeking, anxiety and sensitivity, have been conducted in school settings in order to prevent alcohol and drug use (with no specific reference to tobacco consumption though) in high-risk adolescents [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding research methods, the researchers evaluated the effects of various intervention programs on the externalizing problems of adolescents and found that targeted school-based interventions were more effective (Smedler et al,2015).Furthermore, research have shown that targeted interventions that prevent and reduce adolescent externalizing problems by intervening in personality are both reasonable and feasible (O' Leary-Barrett et al,2016;Edalati et al,2019;Perrier-Ménard et al, 2017). This study was based on activity theory and the theory of ow experience.Using experiential activities (Bell et al, 2014) as the carrier, the researchers designed intervention activities and conducted structured exercises in school to decrease the participating adolescents' externalizing problem behaviors (Mun et al,2015).…”
Section: Methodsmentioning
confidence: 99%
“…Secondary data analysis from the Adventure cluster-randomized trial ( n = 3021) indicated that high-risk adolescents with depression and anxiety symptoms equally benefited from the interventions with regard to reduction in their alcohol use and related problems. Adolescents who reported higher symptoms of externalizing problems (ADHD and conduct problems) at baseline indicated more reduction in alcohol consumption at earlier follow-up periods (6 months post-intervention) and more reduction in their alcohol-related problems over the 24-month period compared to those with lower levels of these problems (58).…”
Section: Effects On Mental Health Problems and Other Relevant Outcomesmentioning
confidence: 99%